Ensuring an independent future for young people with special educational needs and disabilities (SEND): a critical examination of the impact of education, health and care plans in England. Issue 4 (4th July 2018) - Robinson, Deborah; Moore, Nicki; Hooley, Tristram
ABSTRACT: This article examines the implications of the new education, health and care (EHC) planning process for career professionals in England. The new process comes in the wake of a succession of legislation relating to young people with special educational needs and disabilities (SEND) in England. There is much to recommend the new process as it represents a shift to a more holistic and person-centred approach. However, there are four main criticisms which can be made of the new process: (1) the policy has an excessive focus on paid work as an outcome which is unrealistic (for some young people); (2) the resourcing in local authorities is too limited to successfully operationalise the policy; (3) there is a lack of clarity about the professional base delivering EHC planning (especially in relation to the career elements); and (4) the policy is too narrowly targeted. While the new legislation offers some major opportunities, realising these will be difficult. In this paper, questions are raised about the resources required to deliver these services; the responsibilities relevant to such services; and the role and scope of these services in supporting the transitions of vulnerable young people into learning and work in an environment where universal careers provision has been substantially diminished.